Sustainable socioeconomic development service for suburban population: A case study in East Malaysia - Boo Ho Voon; Phang Ing @ Grace; Corina Joseph; Abang Azlan Mohamad; Vloreen Nity Mathew; Kelvin Tee Yong Goh (Accscience publishing, 2023)
Sustainable socioeconomic development service dimensions, determining the suburban residents’ satisfaction from the residents’ perspectives, have yet to be contextually identified for more effective policies and strategies to benefit the targeted households. This case-based empirical research paper aims to examine the relevant sustainable suburban socioeconomic service dimensions from the residents’ perspectives. Interviews and questionnaire survey data were employed to identify the numerous dimensions and items in relevance. Batu Kawa suburban in Kuching (Sarawak, Borneo), Malaysia, was chosen based on its exemplary socioeconomic development and multi-ethnicity. The survey involved 283 respondents. The findings reveal that there were ten dimensions for the sustainable socioeconomic development service dimensions. The findings also indicate that the residents were generally satisfied, but there is still room for further improvement, especially in terms of public transport system, road traffic, safety and security, sport facilities, pollution, and job opportunities. The results suggested that there were differences between two geographical areas separated by the Sarawak River.